2013
DOI: 10.1364/ao.52.006022
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and measurement of optical aberrations of injection molded progressive addition lenses

Abstract: Injection molding is an important mass-production tool in the optical industry. In this research our aim is to develop a process of combining ultraprecision diamond turning and injection molding to create a unique low-cost manufacturing process for progressive addition lenses (PALs). In industry, it is a well-known fact that refractive index variation and geometric deformation of injection molded lenses due to the rheological properties of polymers will distort their optical performance. To address this proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…simulation, [9][10][11][12][13][14][15] multi-shot molding, [10] and runner modifications to improve melt homogenization. [16,17] This work focuses on the mold modification of adding a reusable metal or single-use plastic static mixer to the runner system of a mold.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…simulation, [9][10][11][12][13][14][15] multi-shot molding, [10] and runner modifications to improve melt homogenization. [16,17] This work focuses on the mold modification of adding a reusable metal or single-use plastic static mixer to the runner system of a mold.…”
Section: F I G U R Ementioning
confidence: 99%
“…[ 1,6,7 ] In this way, both the injection molding process and mold are modified. Other novel approaches used for plastic optics include rapid heat cycle molding (RHCM), [ 5 ] conformal cooling systems, [ 8 ] micro‐injection molding, [ 1 ] process optimization and/or defect compensation via simulation, [ 9–15 ] multi‐shot molding, [ 10 ] and runner modifications to improve melt homogenization. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%
“…In this way both the injection molding process and mold are modified. Other novel approaches used for plastic optics include rapid heat cycle molding (RHCM) [5], conformal cooling systems [7], micro-injection molding [1], process optimisation and/or defect compensation via simulation [8-14], multi-shot molding [9], and runner modifications to improve melt homogenisation [15-20].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained indicated that a predefined inhomogeneous refractive index and injectionmolding-induced warpage led to a distorted transmitted wavefront. 17 Moreover, Huang et al 18 conducted numerical simulations of the residual birefringence of injection-molded lenses. Combined with SHWFS experiments, these simulations showed that the transmitted wavefront was affected by refractive index changes and residual birefringence errors in injection-molded aspheric lenses.…”
Section: Introductionmentioning
confidence: 99%